Evaluation of wound healing effect of colostrum and curcumin cream in rat excision wound model - Sakthibalan M; Aakash R; Mangaiarkkarasi A; Prasad C (Journal of Applied Pharmaceutical Research, 2022)
Background: Proper wound healing is very crucial for the reconstruction of injured tissues. Compared to the conventional dressings, currently there are many novel biological wound dressings and healing agents containing colostrum which has many advantages. Aim & Objective: This experimental study was done to evaluate the effect of colostrum and curcumin cream dressing and compare it with that of conventional Povidone iodine dressing. Methods: The rats were anesthetized and excision wounds were created. Wounds were then measured with a standard measuring scale on the day of wounding and then subsequently at a time interval of 4 days till day 20, then on alternate days. After tracing the wound area was treated with the Test and Standard drugs on Day 1,4,8,12,16 and 20. The data was then analysed using Chi square, one-way ANOVA and two tailed t test using Graph pad prism software version 5.0. Results: Efficacy of Colostrum 10% &Curcumin 1% cream (test) was equal to that of povidone iodine 10% (standard) cream with respect to wound contraction and wound healing. But, with respect to the rate of wound healing, Colostrum 10% & Curcumin 1% cream treated group was better compared to the povidone iodine 10% cream treated group. Conclusion: Colostrum plus Curcumin cream has shown a better wound healing at a short time span in excisional wound model in rats, when compared to the conventional povidone iodine cream. Thus, the Colostrum plus curcumin cream appear to be an economical and safe alternative to costly therapies like growth factors for wound healing